Ephesians, power and magic the concept of power in Ephesians in light of its historical setting - Arnold, Clinton E. (Grand Rapids, MI Baker, 1992)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Ephesians -- criticism, interpretation, etc; Magic -- biblical teaching; Powers (Christian theology) -- biblical teaching; Power (Christian theology) -- biblical teaching